Conjugate refractive–reflective homogeniser in a 500× Cassegrain concentrator: design and limits. Issue 4 (1st April 2016) - Shanks, Katie; Baig, Hasan; Senthilarasu, Sundaram; Reddy, K.S.; Mallick, Tapas K.
Abstract : In this study, we present the conjugate refractive reflective homogeniser (CRRH) to be used in a 500× Cassegrain photovoltaic concentrator. The CRRH is a dielectric crossed v‐trough lined with a reflective film whilst maintaining an air gap between them. This air gap between the two surfaces helps in trapping the scattered light from the refractive geometry and ensures both total internal reflection and standard reflection of the escaped rays. A 10–42% drop in optical efficiency has been shown to occur due to varying the surface roughness of the homogeniser in these ray trace simulations for the Cassegrain setup. The CRRH increased the overall optical efficiency by a maximum of 7.75% in comparison with that of a standard refractive homogeniser simulated within the same concentrator system. The acceptance angle and flux distribution of these homogenisers was also investigated. The simple shape of the CRRH ensures easy manufacturing and produces a relatively uniform irradiance distribution on the receiver. The theoretical benefit of the CRRH is also validated via practical measurements. Further research is required but a 6.7% power increase was measured under a 1000 W/m 2 solar simulator at normal incidence for the experimental test.